Vertebral formula and congenital abnormalities of the vertebral column in rabbits. (June 2018) - Proks, P.; Stehlik, L.; Nyvltova, I.; Necas, A.; Vignoli, M.; Jekl, V.
Highlights: Seven different vertebral formulas were identified on examination of radiographs of 330 rabbits. The most common vertebral formula in rabbits was seven cervical, 12 thoracic, seven lumbar and four sacral vertebrae. The prevalence of congenital vertebral abnormalities in rabbits was 15.2%, mostly as a single pathology. The most common vertebral congenital abnormality in rabbits was transitional vertebrae in the thoracolumbar region. The inclination of spinal processes changed from caudal to cranial at thoracic vertebrae T10/T11 in most rabbits. Abstract: The aim of this retrospective study of 330 rabbits (164 males, 166 females) was to determine different vertebral formulas and prevalence of congenital vertebral anomalies in rabbits from radiographs of the cervical (C), thoracic (Th), lumbar (L) and sacral (S) segments of the vertebral column. The number of vertebrae in each segment of vertebral column, position of anticlinal vertebra and localisation and type of congenital abnormalities were recorded. In 280/330 rabbits (84.8%) with normal vertebral morphology, seven vertebral formulas were identified: C7/Th12/L7/S4 (252/330, 76.4%), C7/Th12/L6/S4 (11/330, 3.3%), C7/Th13/L7/S4 (8/330, 2.4%), C7/Th12/L7/S5 (4/330, 1.2%), C7/Th12/L8/S4 (3/330, 0.9%), C7/Th12/L7/S6 (1/330, 0.3%) and C7/Th11/L7/S4 (1/330, 0.3%). The anticlinal vertebra was identified as Th10 in 56.4% of rabbits and Th11 in 42.4% of rabbits. Congenital spinal abnormalities were identified in 50/330 (15.2%) rabbits, predominantly as a single pathology ( n = 44). Transitional vertebrae represented the most common abnormalities ( n = 41 rabbits) in the thoracolumbar ( n = 35) and lumbosacral segments ( n = 6). Five variants of thoracolumbar transitional vertebrae were identified. Cervical butterfly vertebrae were detected in three rabbits. One rabbit exhibited three congenital vertebral anomalies: cervical block vertebra, thoracic hemivertebra and thoracolumbar transitional vertebra. Five rabbits exhibited congenital vertebral abnormalities with concurrent malalignment, specifically cervical kyphosis/short vertebra ( n = 1), thoracic lordoscoliosis/thoracolumbar transitional vertebrae ( n = 1), thoracic kyphoscoliosis/wedge vertebrae ( n = 2) and thoracolumbar lordoscoliosis/thoracolumbar transitional vertebrae/lumbosacral transitional vertebrae ( n = 1). These findings suggest that vertebral columns in rabbits display a wide range of morphologies, with occasional congenital malformations.